Alcoholic fetal syndrome - a problem of the 21st century? - Aleksandra Jaworska-Czerwińska; Elżbieta Bernaciak; Małgorzata Nartowicz; Paulina Farbicka; Magdalena Lemska; Patrycja Banaś; Beata Pilarska; Walery Zukow (Kazimierz Wielki University, 2018)
Fetal Alcohol Syndrome (FAS) is a disease entity that occurs in children who have been exposed to teratogenic alcohol durning fetal life. It includes neurobehavioral abnormalities and changes in the body structure and internal organs. The only reason for the occurrence of this type of disorder is the consumption of alcohol by a pregnant woman (even in small amounts). It is estimated that in Poland about 30% of women consume alcohol in this period (also in small amounts), while in the US every year is born about 40,000 children who are diagnosed with FAS or related disorders.